Experiences of secondary health conditions amongst people with spinal cord injury in South Africa: A qualitative study - Sonti I. Pilusa; Hellen Myezwa; Joanne Potterton (AOSIS, 2021)
Background: Secondary health conditions (SHCs) such as pain, pressure sores, sexual problems, bowel and bladder problems are prevalent throughout the lifespan of people with spinal cord injury (SCI). Studies have reported that SHCs decrease life expectancy and increase health care costs. Studies on the lived experience of SHCs are, however, limited. Objectives: To explore the experiences of SHCs amongst people with SCI in a public rehabilitation hospital in South Africa. Method: Face-to-face semi-structured interviews were conducted with people with SCI from August 2018 to July 2019. All interviews were transcribed verbatim and analysed using a content analysis approach. Results: Seventeen people with SCI were interviewed. Participants experienced a range of SHCs. The most common experienced SHC was pain (94%). The main theme that emerged from the analysis was 'the impact of secondary health conditions on health and well-being'. The categories linked to the impact were SHCs co-occurrence and how SHCs limit function, restrict participation, affect mental health and disrupt lives. Conclusion: We found that SHCs were enormously impactful on our participants' lives and health, as illustrated by their stories of fear, embarrassment and shame. Understanding people with SCI experiences of SHCs can enhance communication between people with SCI and health professionals and may help develop prevention strategies. Clinical implications: To enhance patient-centred care, health professionals are encouraged to actively listen to patients' experiences of illness and the impact on health and wellbeing.